2023
DOI: 10.3390/antibiotics12020387
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Beta-Lactam and Carbapenem-Resistant Bacteria Isolated from Organic Fresh Produce Retailed in Eastern Spain

Abstract: Fresh fruits and vegetables are potential reservoirs for antimicrobial resistance determinants, but few studies have focused specifically on organic vegetables. The present study aimed to determine the presence of third-generation cephalosporin (3GC)- and carbapenem-resistant Gram-negative bacteria on fresh organic vegetables produced in the city of Valencia (Spain). Main expanded spectrum beta-lactamase (ESBL)- and carbapenemase-encoding genes were also detected in the isolates. One hundred and fifteen sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…We observed higher ESBL-PE percentages in samples from organic versus conventionally raised products, both in chicken meat and greens samples. A recent study from Spain supports organic fresh fruits and vegetables as important reservoirs for β-lactam-and even carbapenem-resistant bacteria (Jimenez-Belenguer et al, 2023). Comparable differences in detection rates of ESBL-PE between organic and non-organic grown vegetables have also been previously reported from the Netherlands , and between organic and non-organic chicken meat samples from Germany (Kola et al, 2012) and the Netherlands (Cohen Stuart et al, 2012).…”
Section: Discussionmentioning
confidence: 55%
“…We observed higher ESBL-PE percentages in samples from organic versus conventionally raised products, both in chicken meat and greens samples. A recent study from Spain supports organic fresh fruits and vegetables as important reservoirs for β-lactam-and even carbapenem-resistant bacteria (Jimenez-Belenguer et al, 2023). Comparable differences in detection rates of ESBL-PE between organic and non-organic grown vegetables have also been previously reported from the Netherlands , and between organic and non-organic chicken meat samples from Germany (Kola et al, 2012) and the Netherlands (Cohen Stuart et al, 2012).…”
Section: Discussionmentioning
confidence: 55%
“… 166 In addition, bla NDM (50%) and bla KPC-2 (50%) were the most prevalent carbapenemase genes in CRBs isolated from Chinese rivers. 167 In Spain, Jiménez-Belenguer et al, 168 rather reported bla VIM (26.7%), bla IMP (23.6%), bla OXA-48 (17.4%), bla CMY-2 (8.1%), and bla KPC (4.3%) in CRBs isolated from fresh vegetables. Interestingly, SHV-type carbapenemases, which are often neglected in humans, are well represented (third rank) in animal-environment-food, with 19 variants in this study.…”
Section: Discussionmentioning
confidence: 98%
“…These isolates exhibited the highest phenotypic antimicrobial resistance towards ampicillin, tetracycline, and trimethoprim-sulfamethoxazole. The use of antibiotics in animal feed and as veterinary drugs is increasing, which poses a threat to the entire agriculture ecosystem, including raw vegetable production systems, soil, and groundwater quality [ 35 ]. Our findings suggest that fresh produce vegetables could also serve as a source for multidrug-resistant E. coli .…”
Section: Discussionmentioning
confidence: 99%